Transformasi Kewirausahaan KUBE Kamboja melalui Pemasaran Digital Inovatif Penunjang Wisata Religi di Kelurahan Banjarsari, Surakarta. - Oktiva Anggraini; Nisfatul Izzah; Iva Mindhayani (Universitas Widya Mataram, 2025)
KUBE Kamboja in Kelurahan Banjarsari, Surakarta faces obstacles such as low digital literacy, limited capital, and limited market access. This Beginner Community Empowerment Program aims to encourage women's entrepreneurship and create women-friendly jobs in the development of creative industries in the form of regional souvenirs. The PMP approach integrates training in information technology, entrepreneurship, licensing management (PIRT), digital marketing, and product diversification of souvenirs based on local wisdom. The program results show an increase in KUBE members' understanding of the importance of entrepreneurship and product marketing strategies, which has implications for the progress of MSME businesses. By strengthening the institutional capacity of KUBE through PKM, it is hoped that women will have equal access to economic opportunities and decent work. It is hoped that this program can be replicated by other KUBE and contribute to sustainable women's economic empowerment strategies.